Identification of glycerol as a novel accelerator for sulphur vulcanization of unsaturated rubbers. (March 2022) - Bhadra, Sambhu; Mohan, Nitin; Krishna R, LNVG; Nair, Sujith S
Different organic polyols were investigated as accelerators for different type of vulcanization system such as sulphur, metal oxide, peroxide with different rubbers such as natural rubber (NR), styrene butadiene rubber (SBR), butadiene rubber (BR), butyl rubber (IIR), nitrile rubber (NBR) and chloroprene rubber (CR). Among all the polyols studied, glycerol found to be the most efficient accelerator for sulphur vulcanization of unsaturated rubbers. Moreover, from rheometric study glycerol was found to be reversion free and scorch safe accelerator. A detailed study was performed with glycerol for sulphur vulcanization of silica filled, SBR + BR-based standard passenger car radial (PCR) tire tread compound and plausible mechanism of acceleration was proposed. Finally, from the PCR tyre tread compound 70% of conventional accelerators, namely N-cyclohexyl-2-benzothiazole sulfenamide (CBS) and di-phenyl guanidine (DPG) were replaced with 5 phr (parts per hundred gram of rubber) of glycerol and properties of the vulcanized compounds were measured. The results evidenced that glycerol could efficiently replace 70% conventional accelerators (CBS + DPG), with additional improvement of scorch time by 68%, tensile strength by 31.5%, elongation at break by 75.6% and tear strength by 9.4% of the PCR tyre tread compound. The increase in mechanical properties was due to the improvement in compatibility between silica and rubber in presence of glycerol. Moreover, glycerol is an environmentally benign (nitrogen free, halogen free), fossil free, low-cost material.